2004
DOI: 10.1002/jsfa.1917
|View full text |Cite
|
Sign up to set email alerts
|

Textural changes during cooking of cassava (Manihot esculenta Crantz) roots

Abstract: Consumer acceptability of cassava food products depends mostly on the final texture of the cooked tissue. The age of the roots at harvest seems to be an important factor in determining the final texture. Two cassava cultivars harvested at 8, 17 and 30 months after planting were used for texture loss determination by a puncture test after cooking at constant boiling water temperature. Kinetic data were analysed using fractional conversion. The raw tissue showed decreasing or constant peak yield force values as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…The rate constant K 2 ranged from 0.106 to 0.190 min −1 , indicating the variation in cooking quality among varieties. A varietal influence on the rate constant for cassava harvested at different ages was also observed by Beleia et al, 21,22 who reported ranges of 0.92-0.08 and 0.08-1.06 min …”
Section: Modelling Of Textural Degradationmentioning
confidence: 51%
See 1 more Smart Citation
“…The rate constant K 2 ranged from 0.106 to 0.190 min −1 , indicating the variation in cooking quality among varieties. A varietal influence on the rate constant for cassava harvested at different ages was also observed by Beleia et al, 21,22 who reported ranges of 0.92-0.08 and 0.08-1.06 min …”
Section: Modelling Of Textural Degradationmentioning
confidence: 51%
“…Apart from the physicochemical constituents, tuber texture is also influenced by cell solid content, turgor pressure of the cell, mechanical capacity of deformation of cell walls and cohesiveness provided by the cementing material of the middle lamella and also by the hydration rate of the cooked tubers. 21,22 Eggleston and Asiedu 11 opined that the texture of boiled tubers depends on the interaction between a number of physicochemical properties, and no relationship could be derived between texture and any particular component. The results of the present study also showed that the textural characteristics of cooked cassava tubers cannot be correlated with any specific physicochemical component of the tubers or functional properties of the starch/flour but depend on a number of factors such as the interaction between the components of the tubers and the structural make-up of the tuber tissues.…”
Section: Texture Profile Analysismentioning
confidence: 98%
“…O tempo de cocção foi inferior ao limite crítico de 30 min., proposto por Pereira et al (1985); as raízes, portanto, foram classificadas como de bom cozimento. Beleia et al (2004) A elevação desses índices foi relacionada ao tempo de permanência das raízes tuberosas em campo, sendo verificado incremento diário de 33 kg ha -¹ e 29 kg ha -¹, respectivamente, para produtividade de amido e produção de farinha.…”
Section: Resultados E Discussão Resultados E Discussão Resultados E Dunclassified
“…Since the DH variety was demonstrated as having higher pasting temperature and onset temperatures than bananas belonging to other subgroups , the landrace should require longer cooking times. The water diffusion has also been suggested as a better index for discriminating differences in cooking quality than the instrumental method softening pattern (Beleia et al, 2004). Almeida-Dominguez et al (1997a) also established a relationship between the RVA slope, the rate of water uptake during simmering and the required cooking times.…”
Section: Experimental Data Modelmentioning
confidence: 98%
“…where F RT is the factor of reduction of texture (Beleia et al, 2004). The F RT could either be computed on the basis of textural property at time t instead of infinite time.…”
Section: Kinetic Calculationsmentioning
confidence: 99%